Finite dimensional commutative K-algebras with unity (2016)
This paper is devoted to the study of finite K-algebras i.e. the commutative K-algebras with unity that are finite dimensional vector space over a field K. A finite K-álgebra is direct sum of local finite K-algebras. We obtain a characterization of the local finite K-algebra K[x]/(f(x)) , show that certain finite K-álgebras are isomorphic and discompose the finite K-algebra K[x]/(f(x)) in local finite K-algebras.